The Epidemiology of Peste des Petits Ruminant of Small Ruminants in Sierra Leone - Mustapha, Edwin Idriss; Kargbo, Kabba; Bandabla, Tamba; Kassoh, Fallah Samuel; Yillah, Dauda Sheku (International Journal of Environment, Agriculture and Biotechnology, 2022)
Peste des petits ruminants (PPR) is a major constraint to the productivity of small ruminants in Sierra Leone. The survey aimed to investigate the prevalence of Peste des Petits Ruminants (PPR) and create awareness among livestock farmers on the dangers of the disease to the livestock sector in the study districts. The sampling frame was small ruminants rearing households in Sierra Leone and 298 households were included in the study. A multi-stage sampling was utilized for the selection of individual livestock households. First purposive selection of the five districts, then random selection of chiefdoms, sections, and small ruminant rearing households in the village/locality respectively. Structured questionnaires were developed and administered to the 298 selected households in each locality/village. Data collected were entered into CSEntry using tablets and later imported and stored in the SPSS (version 21). Males are the dominant household heads and most of them went through a non-formal system of education. Goats, chickens, and sheep, are the predominant livestock reared by the households. Many of the respondents can identify the clinical signs and symptoms of PPR, and reported the incident of the disease in their farms. Free range management system in the dries and uncontrolled movement of animals along borderlines are the main sources of PPR outbreaks. The unavailability of vaccines and drugs are principal problem hindering the disease control programmes in the study localities. Though the livestock owners are aware of the morbidity and mortality effects of PPR disease, they have little knowledge of the preventive and treatment measures of the disease on their farms.